Rapid detection and E-test antimicrobial susceptibility testing of Vibrio parahaemolyticus isolated from seafood and environmental sources in Malaysia. - Al-Othrubi, Saleh M.; Hanafiah, Alfizah; Radu, Son; Neoh, Humin; Jamal, Rahaman (Saudi Arabian Armed Forces Hospital, 2011)
Objectives: To find out the prevalence and antimicrobial susceptibility of Vibrio parahaemolyticus in seafoods and environmental sources.